A Systematic Literature Review on Advances in Computer Assisted Instruction - Ahmed, Musa (Online Journal for TVET Practitioners, 2023)
The use of multimedia as a tool for delivering learning content instead of the traditional classroom learning practice is gaining popularity nowadays. CAI is the use of computer programs that are available both online and offline for instruction. The objective of this paper is to conduct a systematic literature review (SLR) on computer assisted (or aided) instruction (CAI) for five years period from 2018 to 2022. This SLR uses review protocol for the selection of primary studies for inclusion in the study from the pool of literature available in the research community. The results of the review shows that the highest publication on CAI in the review period was in 2020 and most researchers used achievement test for collection of data on CAI in the reviewed period. The study also found out that ‘Computer-Based Simulation’ is the popular type of CAI used in experiments by researchers in the period of review. The use of CAI for teaching and learning activities enables flexible and efficient interaction among students and educators. This is a critical factor for enhancing learners’ academic achievement. In conclusion, it is recommended that further research be conducted on CAI to promote its adoption in education systems.